2011 International Conference on E-Business and E-Government (ICEE) 2011
DOI: 10.1109/icebeg.2011.5881617
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain coordination with options contract for the three-level pull supply chain

Abstract: A three-level pull supply chain composed by a manufacturer, a distributor and a retailer is considered to making use of the supply chain management coordination mechanism with options contract. Two models are proposed respectively. One is a supply management mechanism without applying options contract. The other is that with applying options contract. To the two models, corresponding analysis and calculation example are given. The conclusion is presented that the expected total profit with options is more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Ref. [ 41 ] indicated that the total profit of the supply chain with an option contract was more than that without a contract. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [ 41 ] indicated that the total profit of the supply chain with an option contract was more than that without a contract. Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“… The stochastic demand has a risk-neutral equivalent cumulative distribution function , a probability density function , with mean value of µ and variance of [ 47 ]. In equilibrium, supply chain partners have positive demands and profits [ 41 ]. …”
Section: Model Description and Hypothesesmentioning
confidence: 99%